(untitled) (International Journal of Physiotherapy, 2016)
Background: Vertigo is perception of motion, when no movement is present or abnormal perception of motion in response to movement. Vertigo is usually due to a disturbance in the vestibular System. Physical therapy plays an important role in reducing vertigo and nystagmus in benign paroxysmal positional vertigo subjects. Benign paroxysmal positional vertigo(BPPV) comes under the peripheral Vertigo which is the most common disease causing vertigo. Cawthrone and cooksy were the first clinicians to advocate exercises for persons suffering from vertigo. Canalith repositioning procedure was effective in treating BPPV. Brandt Daroff exercises were designed to habituate the central nervous system to provoking position and they dislodge and move the debris out of canal which is effective in treating BPPV. Hence this study compares the effectiveness of these two techniques in treating BPPV. Methods: Total number of 30 subjects was taken and they were divided into two groups by simple random sampling method with Pre test and post test experimental design . Group A subjects were treated with Canalith repositioning procedure and Group B subjects were treated with Brandt Daroff exercises. Outcome measure is dizziness handicap inventory (DHI) Results: P-value is less than 0.05 which shows that there is significant difference between Canalith repositioning procedure and Brandt Daroff exercises. Conclusion: Canalith repositioning procedure is most effective and less time consuming procedure in treating the Benign Paroxysmal positional vertigo subjects and found to have less reoccurrence.